Implementasi Layanan Bimbingan Kelompok dalam Mengatasi Sulit Bergaul pada Siswa Kelas VIII UPT SPF SMP N 1 Patumbak Deli Serdang - Nasution, Ega Putri Andira; Dewi, Ika Sandra; Rijal, Rijal; Tanjung, Nadra Putri Hasina (Invention: Journal Research and Education Studies, 2025)
Difficulty in socializing in adolescents is still a common problem from the past until now. Students who have difficulty socializing will certainly feel some negative impacts that can hinder the effectiveness of life and the optimization of their potential. Therefore, an effort needs to be made to overcome this problem. One effort that can be made is to implement group guidance services. The purpose of this study is to examine in more depth the success of implementing group guidance services in overcoming difficulties in socializing in class VIII students of UPT SPF SMP N 1 Patumbak  Deli Serdang. The research method used is a qualitative research method with a descriptive approach. This study involved a sample of 8 students selected using a purposive sampling technique. The research instruments used were observation and interview guides. After group guidance was given, it was known that there was a change in a more positive direction related to students' socializing abilities. so that it can be understood that the implementation of group guidance was successful in overcoming difficulties in socializing in students.